A Combined Control Strategy Over Full Speed Range of Synchronous Reluctance Motor Considering Iron Loss. Issue 1 (February 2021) - Yang, Yutao; Li, Wenjing; Song, Liangliang; Shen, Chuanwen
Abstract: For the perspective of efficiency optimization and field-weakening speed expansion, the research on the optimal control scheme of SynRM is of great significance. This paper proposes a novel control strategy combined maximum torque per ampere (MTPA) control with maximum efficiency (ME) control, for fast and efficient performance of SynRM considering iron loss. As the speed exceeds the rated speed, maximum torque per voltage (MTPV) control is proposed to realize deep field-weakening. The proposed approach is determined by operating conditions of the motor which avoids the deterioration of dynamic performance due to the switching. In particular, while the working speed is increasing, the control must be able to drive SynRM under the combined MTPA and ME control at first, and then on the MTPV trajectory. In this paper, the current feedback decoupling current control in the SynRM model including the iron loss is developed to compensate the cross-coupling effect for high dynamic control performance. The proposed control strategy has been successfully implemented and verified via MATLAB/Simulink software of a vector control system in changing status.